(untitled) (Revista Contexto & Saúde, 2026)
Objective: To summarize the types of spatial and spatiotemporal analysis technologies used to study syphilis in the context of public health. Methods: This is an integrative literature review that used the PICo strategy to formulate the guiding question: Which scientific studies use spatial and/or spatiotemporal analysis technologies to examine the distribution of syphilis cases? Searches were conducted in the information sources PubMed®, SCOPUS, and Web of Science, as well as in the Virtual Health Library (VHL) on January 16, 2024, using Boolean operators combined with the following keywords: “Syphilis,” “Spatial analysis,” “Spatio-Temporal Analysis,” “Public Health.” The selection was performed using the Systematic Review Support (AReS) software, and studies were included regardless of language or time period, provided they employed an ecological study design. Results: Sixteen articles published since 2010 were analyzed. All used secondary data with an ecological design. Data analysis techniques included area analysis, Bayesian analysis, global and local Moran’s I, sweep statistics, the Prais-Winsten model, and kernel density estimation, with a focus on incidence and prevalence rates, particularly in Brazil. Conclusion: It became evident in the studies that syphilis is not limited to the occurrence of cases alone but is also related to socio-spatial factors that influence its occurrence in time and space, such as socioeconomic inequalities, social vulnerabilities, and access to health services.